2016
DOI: 10.1111/1440-1681.12610
|View full text |Cite|
|
Sign up to set email alerts
|

Protein tyrosine phosphatase PTPRB regulates Src phosphorylation and tumour progression in NSCLC

Abstract: Protein tyrosine-phosphatases (PTPs) play important roles in various biological processes. Deregulation in PTP function has been implicated in carcinogenesis and tumour progression in many cancer types. However, the role of protein tyrosine phosphatase receptor type B (PTPRB) in non-small-cell lung cancer (NSCLC) tumorigenesis has not been investigated. Lentiviral vector expressing PTPRB cDNA or shRNA was infected into A549 and H1299 cell lines, followed by cell proliferation, colony formation, soft agar and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
(53 reference statements)
1
21
0
Order By: Relevance
“…A study by Hu et al (33) demonstrated that miR-665 exerts promoting effects on hepatocellular carcinoma cell proliferation, migration and invasion by directly targeting PTPRB and through the Hippo signaling pathway. Interestingly, PTPRB has been found to suppress NSCLC cell proliferation and invasion by inhibiting the phosphorylation of the proto-oncogene tyrosine-protein kinase Src (36). In the present study, the binding site of miR-665 was predicted in the 3'-UTR of PTPRB, confirming that PTPRB was a direct target gene of miR-665 in NSCLC.…”
Section: Multivariate Analysis --------------------------------------supporting
confidence: 73%
“…A study by Hu et al (33) demonstrated that miR-665 exerts promoting effects on hepatocellular carcinoma cell proliferation, migration and invasion by directly targeting PTPRB and through the Hippo signaling pathway. Interestingly, PTPRB has been found to suppress NSCLC cell proliferation and invasion by inhibiting the phosphorylation of the proto-oncogene tyrosine-protein kinase Src (36). In the present study, the binding site of miR-665 was predicted in the 3'-UTR of PTPRB, confirming that PTPRB was a direct target gene of miR-665 in NSCLC.…”
Section: Multivariate Analysis --------------------------------------supporting
confidence: 73%
“…Targetscan and miRanda were used to analyze potential miR-665 targets. Among them, we were particularly interested in PTPRB, because the PTPR family is mostly regarded as tumor suppressors in carcinogenesis and cancer development 16 . RT-qPCR was used to analyze PTPRB expression in 50 paired HCC tissues and adjacent normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosine phosphatase receptor type B (PTPRB) is a potential target of miR-665(predicted by TargetScan and miRanda). Recent studies have also discovered that PTPRB may function as a tumor suppressor in carcinogenesis and cancer development 16 . However, a functional link between the miR-665/PTPRB axis and Hippo signaling pathway in association with HCC proliferation, migration, and invasion remains to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…It was downregulated and was significantly associated with OS in NSCLC patients. Besides, PTPRB regulated the tumorigenesis and Scr phosphorylation . Weng et al reported that PTPRB promoted tumor metastasis and invasion of colorectal cancer via inducing epithelial mesenchymal transition.…”
Section: Discussionmentioning
confidence: 98%